Nutrient balance under wheat-mungbean-T. Aman cropping pattern in calcareous soils of Bangladesh - Quddus, MA; Mian, J Abedin; Naser, HM; Hossain, MA; Salauddin, AKM (Bangladesh Journal of Agricultural Research, 2017)
Field experiments on Wheat-Mungbean-T. aman cropping pattern were conducted at Regional Pulses Research Station (RPRS), Madaripur in calcareous soils under Low Ganges River Floodplain (?EZ-12) during 2009 to 2010 to prepare nutrient balance sheet for the cropping pattern and fertilizer recommendation for study area. The treatments were T1= Control; T2 = Farmers practice; T3 = AEZ based recommended fertilizer dose and T4 = Soil test based fertilizer dose. The experiment was laid out in RCBD with three replications. Results revealed that the average yields of wheat, mungbean and T. aman ranged from 1517 to 3124 kg ha-1, 1320 to 1863 kg ha-1 and 2974 to 4859 kg ha-1, respectively. Grain yield of all crops increased significantly higher in soil test based (STB) fertilizer treatment (T4) over the other treatments. Among the major nutrients, the magnitude of negative balance was greater with N and K followed by Mg and Ca. The negative balance of N (-56.0 to -183 kg ha-1), K (- 71.0 to -167 kg ha-1), Ca (-7.50 to -27.1 kg ha-1), and Mg (-16.7 to -35.7 kg ha-1) was observed in all the managements might be due to added lower amount of nutrients in soil and higher removal by the crops from the soil. Positive balance of P indicated that the added amount of P is larger than the removal; P fertilization was enough to make apparent balances positive. Across various treatments, there was some amount of positive apparent S balance except absolute control plots and farmers practice. On the other hand, Zn and B balance in the system was neutral to slightly positive. Results revealed that, N, K, Ca, and Mg balance after two years of cropping was negative regardless of soil type and management strategies adopted. There was an improvement in organic matter in all treatments where biomasses of mungbean were incorporated. Organic matter, N, P, S, Zn and B status in soil was improved due to soil test based fertilization over the initial status. Considering the gross margin and soil fertility the soil test based (STB) fertilizer management practice is economically profitable and sustainable. Bangladesh J. Agril. Res. 42(1): 121-136, March 2017